PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP HARGA SAHAM PADA BANK HIMBARA - Prayodana, Hangga; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2024)
The capital market is a place for investors to channel funds in the form of shares with the aim of investing. There are various internal and external factors that can influence Himbara Bank's stock price. The aim of this research is to determine the influence of GCG, firm size and inflation on firm performance and stock prices. This research uses quantitative analysis. In this research, the data analysis technique used is panel data path analysis. The data used is secondary data, using a time series from 2013-2022. The research results found that GCG partially influences firm performance. Firm size influences firm performance. Inflation affects firm performance. Firm size influences stock prices. Inflation has no effect on stock prices. Firm performance influences stock prices. Firm performance mediates firm size on stock prices. Firm performance does not mediate inflation on stock prices.